An Investigation into Factors Impacting on Customer Decision to Adopt E-Banking: Viewpoints of GCB Customers - Obeng-Ayisi, Emmanuel; Quansah, Charles; Mensah, Ronald Osei; Acquah, Andrews (Technium Social Sciences Journal, 2022)
This study was focused on evaluating the factors influencing the decision of customers of GCB bank on the adoption of e-banking. The study used a descriptive design where a structured questionnaire was administered to 351 customers of five selected GCB bank branches in the Kumasi Metropolis using convenient sampling technique. Data was analysed using the Statistical Package for Social Sciences (SPSS) version 20 software. It was identified that although people have knowledge about e-banking, their focus on using it is a bit questionable. For instance, customers are much more conversant in the use of SMS banking and ATM as compared to their conversant use of credit cards, internet banking and phone banking. In terms of the useful features of e-banking that necessitates its adoption by customers, e-banking was seen as convenient, easily accessible, easy to use, useful, advantageous and highly secured. However, issues of inadequate education, huge security issues, high illiteracy, network failure, inadequate governmental policies and slow response from the bank are possible in curtailing the frequent adoption of the services by customers of the bank. Therefore, the management of the bank should put in structures and measures to make the e-banking platforms adopted by the bank more user friendly for customers to subscribe to the products.